Made in Germany Technologie, Geschichte, Kultur - Made in Germany: History and Technology; Katzir, Shaul 1970-; Schaefer, Sagi 1970-; Shaḥar, Galili 1970-; Wallstein-Verlag; Workshop: Made in Germany (Tel Aviver Jahrbuch für deutsche Geschichte, 2020)
Hinweis Internationale Hölderlin Bibliographie: "The articles in this volume, some of which were first presented at an international workshop held at Tel Aviv University in June 2019" (Seite 10)